2019
DOI: 10.1088/1361-6587/ab4d0c
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced electron acceleration in aligned nanowire arrays irradiated at highly relativistic intensities

Abstract: We report a significant enhancement in both the energy and the flux of relativistic electrons accelerated by ultra-intense laser pulse irradiation (>1×10 21 W cm −2 ) of near solid density aligned CD 2 nanowire arrays in comparison to those from solid CD 2 foils irradiated with the same laser pulses. Ultrahigh contrast femtosecond laser pulses penetrate deep into the nanowire array creating a large interaction volume. Detailed three dimensional relativistic particle-in-cell simulations show that electrons or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 50 publications
0
18
0
Order By: Relevance
“…The high aspect ratio between length and diameter of NWs favors an increased laser absorption due to a greater effective interaction surface area with the incoming electromagnetic (EM) wave, occurring within a few laser cycles such as to maximize the interaction with the intact NW forest. This increased interaction ejects electrons from the NW boundaries mainly through Brunel-type and absorption processes, which are further accelerated in the gaps between the NWs by Direct Laser Acceleration (DLA) before re-collision with the target bulk 49 , where the electrons seed a cascade of impact ionization events. This leads to a denser and hotter electron cloud at the rear side of the target and generates a more intense accelerating sheath electric field driving the TNSA mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…The high aspect ratio between length and diameter of NWs favors an increased laser absorption due to a greater effective interaction surface area with the incoming electromagnetic (EM) wave, occurring within a few laser cycles such as to maximize the interaction with the intact NW forest. This increased interaction ejects electrons from the NW boundaries mainly through Brunel-type and absorption processes, which are further accelerated in the gaps between the NWs by Direct Laser Acceleration (DLA) before re-collision with the target bulk 49 , where the electrons seed a cascade of impact ionization events. This leads to a denser and hotter electron cloud at the rear side of the target and generates a more intense accelerating sheath electric field driving the TNSA mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…Optical field ionization initially generates a plasma concentrated at the tip of the NWs. The electrons ripped from the material are accelerated in the space between the NWs by a strong ponderomotive interaction [29] . The accelerated electrons are characterized by a three times higher electron temperature and an integrated flux 22 times larger with respect to foil targets [29] .…”
Section: Introductionmentioning
confidence: 99%
“…The electrons ripped from the material are accelerated in the space between the NWs by a strong ponderomotive interaction [29] . The accelerated electrons are characterized by a three times higher electron temperature and an integrated flux 22 times larger with respect to foil targets [29] . Electrons accelerated in the laser backward direction form a space charge sheath in front or the target, where ions are accelerated to multi-megaelectronvolt energy towards the laser by transverse normal sheath acceleration (TNSA) [30] .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, relativistic interaction of ultrashort laser pulses with nano-or micro-structured targets has attracted interest, mainly because of the enhanced efficiency of laser absorption. Depending on the target geometry, the improved laser-target coupling can result in a volumetric heating of the plasma up to extreme temperatures [5], in a more efficient x-ray emission [6] or in an efficient production of HE [7][8][9]. It was shown that for aligned arrays of micropillars or microchannels, the interaction can lead to mega-Ampere currents of relativistic electrons propagating into the target [10], resulting in the self-generation of a mega-Gauss magnetic field on its rear surface [11].…”
Section: Introductionmentioning
confidence: 99%